PENGARUH LITERASI INFORMASI DAN PENGUATAN PENDIDIKAN KARAKTER TERHADAP KINERJA GURU SMP NEGERI DI KECAMATAN KUANTAN MUDIK KABUPATEN KUANTAN SINGINGI - Gunawan, Hendri; Mustafa, M. Nur; Natuna, Daeng Ayub; Wahyuni, Try (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2021)
This study aims to analyze; 1) the effect of information literacy on teacher performance at SMP Negeri Kecamatan Kuantan Mudik Kabupaten Kuantan Singingi; 2) the effect of strengthening character education on teacher performance at SMP Negeri Kecamatan Kuantan Mudik Kabupaten Kuantan Singingi; 3) the effect of information literacy and strengthening character education on teacher performance at SMP Negeri Kecamatan Kuantan Mudik Kabupaten Kuantan Singingi. This study uses a quantitative approach with the type of ex post facto research. This study examines three variables to be studied to determine how much influence the independent and dependent variables have. The population in this study were 116 teachers and the sample in this study was 90 teachers SMP Negeri Kecamatan Kuantan Mudik Kabupaten Kuantan Singingi. The data analysis technique used is descriptive statistical analysis and inferential statistical analysis. The results of the study found that; 1) there is a significant and positive influence between information literacy variables on teacher performance at SMP Negeri Kecamatan Kuantan Mudik Kabupaten Kuantan Singingi; 2) there is a significant and positive effect between strengthening character education on teacher performance at SMP Negeri Kecamatan Kuantan Mudik Kabupaten Kuantan Singingi; and 3) obtained a significant effect between the variables of information literacy and strengthening character education on teacher performance at SMP Negeri Kecamatan Kuantan Mudik Kabupaten Kuantan Singingi.